(untitled) (Rheumatology Reports, 2011)
Multiple myeloma (MM) is a malignant monoclonal proliferation of plasma cells usually showing bone involvement with predilection of the spine. The cervical spine is the least common site of disease involvement. We report the case of 72-year-old man presenting with progressively increased cervical pain, associated with sciatica and disturb walking. In the neurological exam, there was a quadripyramidal syndrome, and superficial sensory disturbance. The X- ray examination of the cervical spine showed lytic lesions of C2. A tumoral process was found by magnetic resonance imaging (MRI) compressing the spinal cord at the level of C4 with osteolysis of the posterior arch. An open surgery was performed. Microscopic examination and immunohistochemical studies confirmed the diagnosis of multiple myeloma of kappa subtype. Immunoelectrophoresis revealed the presence of immunoglobulin G kappa. The patient was diagnosed as having MM with cervical vertebra involvement and he has started chemotherapy.